HETEROGENEITIES OF SUBCONTINENTAL LITHOSPHERIC MANTLE AT THE SOUTHERNMOST OF SOUTH-AMERICAN PLATE: INFLUENCE OF PRESENT SUBDUCTION AND LITHOSPHERE-ASTENOSPHERE INTERACTIONS UNDER THE PALI AIKE VOLCANIC FIELD - GERVASONI, Fernanda; CONCEIÇÃO, Rommulo V.; JALOWITZKI, Tiago L. R.; SCHILLING, Manuel E.; ORIHASHI, Yuji; NAKAI, Shun'ichi; SYLVESTER, Paul (Pesquisas em Geociências, 2012)
The Pali Aike Volcanic Field is located in southern South America where there is a complex tectonic system due to interactions between the Nazca, Antarctica and Scotia oceanic plates with the South-American continental plate, and due to the proximity of the Chile ridge (Chile Triple Junction). This volcanic field has basanites, alkali basalts and pyroclastic rocks that host garnet- and spinel peridotites that may also bear phlogopite and pargasite. The mantle xenoliths of this study are from the Laguna Timone maar, located in Pali Aike, being predominantly garnet-spinel lherzolites, spinel lherzolites, garnet-spinel harzburgites, and one glimmerite. The paragenesis garnet+spinel+Ti-phlogopite+K-paragsite is present in the studied samples and suggests an origin from the garnet-spinel peridotite transition zone in the upper mantle. Partial melting events are inferred from the negative correlations between major elements and #Mg, as well as, from the light REE < heavy REE of garnet-spinel harzburgites pattern, and from the heavy REE depletion in spinel lherzolites that, as suggested by trace-element modelling underwent up to 16% partial melt (no-modal batch melting). The garnet-spinel lherzolites have trace element values similar to Primitive Mantle, with characteristics of “fertile” mantle. All mantle xenoliths have enrichments in chalcophile elements (W, Pb, Mo, Sn) which are attributed to present subduction of Antarctica plate under the South-American plate. The occurrence of glimmerite, the presence of hydrated minerals (phlogopite and pargasite) in peridotites, and the geochemical similarities with peridotites metasomatised by ascending asthenospheric melts (peridotites of the Manzaz, Argelia, and peridotites of the Vitim Volcanic Field, Baikal, Siberia), such as Ba/Nb, Ba/La and U/Nb ratios, suggest metasomatism by asthenospheric fluids. These asthenosphere-lithosphere interactions occurred due to the upwelling of the underlying asthenospheric mantle when the Chile Triple Junction was at the same latitude ...